ANALISIS PEMELIHARAAN MESIN PRODUKSI DENGAN MENGGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE PADA CV KUSUMA ARGA MUKTI DI YOGYAKARTA - Refica Yulianti; Erni Widajanti (JSE: Jurnal Sharia Economica, 2026)
CV Kusuma Arga Mukti is a limestone quarrying and processing company that operates six main production machines. Based on 2024 operational data, the company recorded 67 machine failure incidents with a cumulative downtime of 48.64 hours per year. The maintenance system currently in place is predominantly corrective in nature, meaning repairs are only carried out after failures occur, making it incapable of proactively preventing breakdowns. This study aims to analyze the implementation of the Reliability Centered Maintenance (RCM) method as a maintenance strategy. Quantitative data were obtained through direct field observation, in-depth interviews, and company documentation. The analytical stages encompass System Work Breakdown Structure (SWBS), Failure Mode and Effect Analysis (FMEA), Logic Tree Analysis (LTA), and maintenance task selection. FMEA results reveal that the Jaw Crusher body/frame holds the highest Risk Priority Number (RPN = 294), followed by the toggle plate assembly (RPN = 280) and the Bucket Conveyor chain (RPN = 252). LTA findings classify most Failure Modes under Category B (Outage Problem) and Category A (Safety Problem). The recommended maintenance tasks include Time Directed (TD), Condition Directed (CD), and Finding Failure (FF) approaches. The application of RCM is expected to transform the company's maintenance orientation from reactive to proactive, thus reducing machine failure frequency, minimizing unplanned downtime, and sustaining long-term reliability improvement.